Reconstructive and reproductive surgery in gynecology. Volume one, Fundamentals and Conditions - Munro, Malcolm G.; Gomel, Victor (Boca Raton, FL : CRC Press, 2019)
This new edition of a groundbreaking book, now in two volumes,enables the readermore readily to understand pathogenesis, appropriate investigation, and application of both surgical and nonsurgical strategies and techniques.
OCLC-licensed vendor bibliographic record.
Keywords: Generative organs, Female -- Surgery; Infertility, Female -- Surgery; Surgery, Plastic; MEDICAL / Gynecology & Obstetrics; MEDICAL / Reproductive Medicine & Technology